2017
DOI: 10.1074/jbc.m116.753772
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin E is a fungal global transcriptional regulator that determines the transition from the primary growth to the stationary phase

Abstract: In response to limited nutrients, fungal cells exit the primary growth phase, enter the stationary phase, and cease proliferation. Although fundamental to microbial physiology in many environments, the regulation of this transition is poorly understood but likely involves many transcriptional regulators. These may include the sirtuins, which deacetylate acetyllysine residues of histones and epigenetically regulate global transcription. Therefore, we investigated the role of a nuclear sirtuin, sirtuin E (SirE),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 48 publications
2
33
1
Order By: Relevance
“…A transcriptomic study of the sirA deletion mutant showed both up and down regulated secondary metabolite BGCs, and measured increases in austinol and sterigmatocystin production (Itoh et al, 2017b). Another class I sirtuin SirE (AN1226) has also been studied in A. nidulans, and was found to regulate both primary and secondary metabolism (Itoh et al, 2017a). Deletion of sirE led to an increase in H3K9ac, H3K18ac, as well as H3K56ac during various growth conditions (Itoh et al, 2017a).…”
Section: Erasing the Codementioning
confidence: 99%
See 1 more Smart Citation
“…A transcriptomic study of the sirA deletion mutant showed both up and down regulated secondary metabolite BGCs, and measured increases in austinol and sterigmatocystin production (Itoh et al, 2017b). Another class I sirtuin SirE (AN1226) has also been studied in A. nidulans, and was found to regulate both primary and secondary metabolism (Itoh et al, 2017a). Deletion of sirE led to an increase in H3K9ac, H3K18ac, as well as H3K56ac during various growth conditions (Itoh et al, 2017a).…”
Section: Erasing the Codementioning
confidence: 99%
“…Another class I sirtuin SirE (AN1226) has also been studied in A. nidulans, and was found to regulate both primary and secondary metabolism (Itoh et al, 2017a). Deletion of sirE led to an increase in H3K9ac, H3K18ac, as well as H3K56ac during various growth conditions (Itoh et al, 2017a).…”
Section: Erasing the Codementioning
confidence: 99%
“…Hypoxia induces biosynthesis of the secondary metabolite pseurotin A in the airborne fungal pathogen A. fumigatus [75]. SirE is a recently discovered NAD +dependent deacetylase that represses A. nidulans events during the stationary growth phase (that mammals and yeasts lack), autolysis, conidia development, secondary metabolites and extracellular hydrolase production [76].…”
Section: Cellular Nucleotides and Glycolytic Mechanisms Regulated By Nudix Hydrolase A Under Hypoxiamentioning
confidence: 99%
“…We recently reported that the gene disruption of SirA increases sterigmatocystin production by A. nidulans cultured in liquid GMM medium (Itoh et al, 2017b). To determine the potential of 5-methylmellein to alter fungal secondary metabolism, A. nidulans was cultured in GMM medium with or without 100 mM 5-methylmellein for one week, and then the culture broth was extracted with ethyl acetate and analyzed by HPLC.…”
Section: Effect Of 5-methylmellein On Fungal Secondary Metabolismmentioning
confidence: 99%
“…This result was unexpected since 5methylmellein inhibits SirA in vitro, and suggests that 5methylmellein targets another sirtuin isozyme(s) that regulates sterigmatocystin production. SirE of this fungus could be the most likely candidate since its gene disruption decreases sterigmatocystin production (Itoh et al, 2017b) and might cancel the possible positive effect of 5methylmellein on sterigmatocystin production through SirA inhibition. The amounts of metabolites at retention times of 6.9, 12.8, 18.2 and 19.8 min were increased > 1.5-fold by 5-methylmellein (P < 0.03) ("1" in Figs.…”
Section: Effect Of 5-methylmellein On Fungal Secondary Metabolismmentioning
confidence: 99%